(untitled) (Aksioma Education Journal, 2025)
Kawung batik motif is one of Indonesia’s cultural heritage that is full of philosophical and aesthetic meanings, and shows regular and symmetrical visual patterns. This research aims to analyze the geometric shapes in Kawung motif and identify the types of geometric transformations that form the pattern arrangement. The approach used in this research is descriptive qualitative method with geometric visual analysis technique. Data were obtained through documentation study of Kawung motif, visual observation of the pattern arrangement, and literature study related to geometric transformation theory. The results show that Kawung motifs contain four types of geometric transformations, namely translation (repetition of patterns horizontally and vertically), rotation (rotation of 90° and 180° towards the center point), reflection (reflection on the vertical and horizontal axes), and dilation (variation in the size of motif elements). Folding symmetry and rotating symmetry were also found to be part of the visual structure that reinforces the regularity of the motif. These findings show that the Kawung motif has a mathematical value that can be explained scientifically, in line with the principles of plane geometry. The conclusion of this study confirms that Kawung batik motifs can be utilized as contextual media in mathematics learning, especially for geometry transformation materials. Thus, the integration between local culture and science through this visual approach not only supports meaningful and applicable learning, but also becomes part of the strategy of cultural preservation through education